The Effect of Using Insulation on the Energy Saving in Building - Ihsan F. Abbas; Jawdet Al Yaqub (Tikrit Journal of Engineering Sciences, 2013)
The aim of the present study is to analyze the thermal performance of a building which is of 600 m3 size. The building is built in three different models. In the first model, walls are built with brick. In the second model, a layer of foam (Polystyrene) of 4 cm thickness has been used as an insulation layer inside walls and on the roof. In the third model, walls are constructed from two parts separated by air gap of 8 cm wide; moreover a secondary roof is added to this model. A Qbasic program is prepared to simulate the required mathematical equations in finite difference method and the weather conditions data of Baghdad city at January, 1994. The results of the simulation showed that the ratio of the saved energy by the second and third models with respect to the first model are 29.96%, and 35.40% respectively.